(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research examines how consumer trust in fintech platforms influences the adoption of fintech services in regions with low banking penetration. Using a Systematic Literature Review (SLR) approach, this research explores current literature to identify the factors that shape consumer trust, as well as their impact on fintech adoption decisions. The main findings show that data security, transaction transparency, service provider reputation, customer support, and user experience are crucial factors that influence the level of consumer trust. Consumer trust has proven to be a key driver in fintech adoption, while low trust is often a barrier. This research also identifies differences in the influence of consumer trust based on population segments, as well as the role of local policies and regulations in shaping consumer trust. The implications of this research include suggestions for developing policies and practical strategies in the fintech industry to increase financial inclusion in regions with low banking penetration.